Molecular Insights into Acne Vulgaris: A Multi-Omics Approach Towards Precision Medicine - Ikawati, Hartanti Dian; Fadilah; Fitria Agustina (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Acne vulgaris is a common dermatological disorder that significantly impacts quality of life, yet its complex pathogenesis remains incompletely understood, contributing to the variability in clinical presentation and treatment response. This review summarizes recent advances in omics-based research on acne vulgaris and explores how these findings support the development of targeted therapy. A systematic literature search was conducted in PubMed using the keywords “acne genomic,” “acne transcriptomic,” “acne proteomic,” and “acne metabolomic.” Original research articles published in English, available in full text, and published between 2015 and 2025 were included. After screening for relevance and removing duplicates, 17 studies met the inclusion criteria. Additional relevant articles were also referenced to complement the discussion. The selected studies show that large-scale molecular analysis provides a more comprehensive understanding of the molecular mechanisms underlying acne vulgaris. These findings enable the identification of novel biomarkers, better insight into pathological pathways, and the development of more targeted therapeutic strategies. Further studies are needed to validate these findings and translate them into improved strategies for the diagnosis, prevention, and treatment of acne vulgaris.